2019
DOI: 10.1002/1873-3468.13520
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic histology using machine learning for nonalcoholic fatty liver disease

Abstract: Histopathology requires the expertise of specialists to diagnose morphological features of cells and tissues. Raman imaging can provide additional biochemical information to benefit histological disease diagnosis. Using a dietary model of nonalcoholic fatty liver disease in rats, we combine Raman imaging with machine learning and information theory to evaluate cellular‐level information in liver tissue samples. After increasing signal‐to‐noise ratio in the Raman images through superpixel segmentation, we extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…However, evaluation of myocardial viability for determining the surgical procedures has hitherto been performed only by limited modalities, i.e., myocardial scintigraphy and gadolinium-enhanced magnetic resonance imaging, both of which are utilized only preoperatively and not available for precise intraoperative evaluation [ 11 , 38 ]. Regarding this issue, Raman spectroscopic analysis may be a promising candidate, which provides clues to identify the molecular structure of substances without using any specific chemical labeling, e.g., by fluorescent dyes [ 14 , 15 , 17 , 21 , 29 , 33 ]: specific Raman shifts in Raman spectrum acquired under green light excitation can be used to unveil changes of molecules such as reduced cytochromes c and b, oxygenated myoglobin and lipids [ 1 , 6 , 20 , 31 ]. We have previously demonstrated that myocardial ischemia and infarct could be detected quantitatively by Raman scattering light, which represents the energy states of molecular vibrations [ 26 , 27 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, evaluation of myocardial viability for determining the surgical procedures has hitherto been performed only by limited modalities, i.e., myocardial scintigraphy and gadolinium-enhanced magnetic resonance imaging, both of which are utilized only preoperatively and not available for precise intraoperative evaluation [ 11 , 38 ]. Regarding this issue, Raman spectroscopic analysis may be a promising candidate, which provides clues to identify the molecular structure of substances without using any specific chemical labeling, e.g., by fluorescent dyes [ 14 , 15 , 17 , 21 , 29 , 33 ]: specific Raman shifts in Raman spectrum acquired under green light excitation can be used to unveil changes of molecules such as reduced cytochromes c and b, oxygenated myoglobin and lipids [ 1 , 6 , 20 , 31 ]. We have previously demonstrated that myocardial ischemia and infarct could be detected quantitatively by Raman scattering light, which represents the energy states of molecular vibrations [ 26 , 27 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Raman microscopy is, therefore, a powerful tool for the investigation of lipids in cells and tissues 10 15 . Although some researchers applied the Raman microscopy to NAFLD 16 18 , the efficacy of Raman microscopy for the investigation of NAFLD is still under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Minamikawa et al demonstrated the difference in chemistry between large and small LDs in a nonalcoholic steatohepatitis (NASH) model mice [ 20 ]. In our previous study, we combined Raman imaging with machine learning to evaluate NAFLD liver tissue samples in rats and grouped tissues with similar composition, providing a descriptor that enabled inference of tissue states, thus contributing valuable information to histological inspection of NAFLD [ 11 ]. However, it is unclear whether spontaneous Raman microscopy is applicable to the evaluation of the nascent state of NAFLD; the morphological features of NAFLD are not clear in this state and the intensity of spontaneous Raman scattering light is generally weak [ 9 ].…”
Section: Introductionmentioning
confidence: 99%